1977
DOI: 10.1073/pnas.74.11.4881
|View full text |Cite
|
Sign up to set email alerts
|

Role of nucleotides in tubulin polymerization: effect of guanylyl 5'-methylenediphosphonate.

Abstract: Incubation of 48,000 X g rat brain supernatants for 30 min at 37 degrees with 1-2 mM guanylyl 5'-methylenediphosphonate [Gmp(CH2)pp] results in polymerization of 95-98% of the tubulin present. This is considerably more than the 50% polymerization that can be achieved with the natural nucleotide, GTP, under optimal conditions. Gmp(CH2)pp is also much more effective than GTP in inducing polymerization of purified tubulin. Assembly of microtubules with Gmp(CH2)pp occurs at tubulin concentrations one-third of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
4

Year Published

1981
1981
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 20 publications
5
35
4
Order By: Relevance
“…The most convincing evidence that GTP hydrolysis modulates microtubule dynamics has come from comparison of the behavior of microtubules containing nonhydrolyzable GTP analogues and GDP. The GTP analogue GMPCPP, which is susceptible to hydrolysis because the methylene bridge finks the alpha and beta phosphate residues, is unique in binding relatively (Zeeberg and Caplow, 1979). tightly to the tubulin E-site and in being more effective than GTP in promoting assembly (Sandoval et al, 1977;Hyman et al, 1992). It is of special interest that the rate of tubulin subunit dissociation from microtubules is dramatically increased when the gamma phosphate moiety of a bound NTP has been lost by hydrolysis.…”
Section: Regulation Of Microtubule Dynamics By Controlled Hydrolysis mentioning
confidence: 99%
See 1 more Smart Citation
“…The most convincing evidence that GTP hydrolysis modulates microtubule dynamics has come from comparison of the behavior of microtubules containing nonhydrolyzable GTP analogues and GDP. The GTP analogue GMPCPP, which is susceptible to hydrolysis because the methylene bridge finks the alpha and beta phosphate residues, is unique in binding relatively (Zeeberg and Caplow, 1979). tightly to the tubulin E-site and in being more effective than GTP in promoting assembly (Sandoval et al, 1977;Hyman et al, 1992). It is of special interest that the rate of tubulin subunit dissociation from microtubules is dramatically increased when the gamma phosphate moiety of a bound NTP has been lost by hydrolysis.…”
Section: Regulation Of Microtubule Dynamics By Controlled Hydrolysis mentioning
confidence: 99%
“…4). The previous failure to form microtubnles in a reaction of purified tubulin with GMPCP (Sandoval, 1977) probably resuited from use of low protein concentrations. Video microscopy was used to measure the elongation rate with GMPCP.…”
Section: Stability Of Gmpcp-microtubulesmentioning
confidence: 99%
“…On the other hand, GTP can be substituted by non-hydrolyzable GTP analogues. [17][18][19] Further, it does not seem that the rate of GTP hydrolysis is in proportion to the rate of polymerization of the tubulin-colchicine complex and microtubule assembly from pure tubulin. 21,22,24) We found that GTP was hydrolyzed in the stage of tubulin oligomer formation before microtubule assembly.…”
Section: Discussionmentioning
confidence: 99%
“…16) At the non-exchangeable site, GTP is tightly bound to tubulin. Non-hydrolyzable GTP analogues [17][18][19] are available instead of GTP. In addition, it has been reported that GTP is required for the polymerization of the tubulin-colchicine complex as well as for microtubule formation.…”
mentioning
confidence: 99%
“…According to one interpretation, bundling of microtubules by MAP2 and tau involves their forming dimers in the cytoplasm and thus actively cross-linking the adjacent microtubules to which they are bound (Kanai et al, 1989;Lewis et al, 1989). The alternative view is based on the observation that microtubules in nonneuronal cells that do not express MAP2 or tau are also bundled by a variety of chemically dissimilar stabilising agents, including taxol, GTP analogues, and dimethyl sulfoxide (DMSO) (Sandoval et al, 1977;Schiff and Horwitz, 1980;Weisshaar et al, 1992). From this it has been argued that bundling by MAPs reflects their property of stabilizing microtubules, which are then bundled by other ubiquitous cellular proteins (Chapin et al, 1991) or because they have an intrinsic affinity for one another (Lee and Brandt, 1992) or because they are brought together by physical interactions within the cell (Matus, 1991;Weisshaar et al, 1992).…”
Section: Introductionmentioning
confidence: 99%